No support for solar radiation as a major evolutionary driver of malar stripes in falcons - Michelle Vrettos; Chevonne Reynolds; Arjun Amar (Journal of Avian Biology)
The malar stripes of falcons (Falco spp.) are often hypothesised to function by reducing the amount of solar glare reflected into the falcon's eyes while hunting, thereby aiding foraging efficiency in bright conditions. This ‘solar glare hypothesis' is supported by intraspecific trends in peregrine falcons Falco peregrinus, in which populations inhabiting regions of higher average annual solar radiation exhibit larger and darker malar stripes on average. Here, we extend the methodological approach previously used in peregrine falcons to examine both intra‐ and interspecific relationships between solar radiation and malar stripe morphology across all extant falcon species, thereby providing a more robust test of the hypothesis that falcon malar stripes evolved as an adaptation against negative visual effects of solar glare. We obtained web‐sourced photographs of all extant falcon species, taken across each species' geographic range, and related mean breeding season solar radiation at each photograph location to the size and darkness of the birds' malar stripes, simultaneously testing for intraspecific and interspecific relationships between malar stripe characteristics and solar radiation, and including phylogeny and relevant ecological traits as covariates. We found no consistent interspecific relationship between solar radiation and malar stripe characteristics Likewise, in 38 out of 39 species, malar stripe characteristics were not positively intraspecifically related to solar radiation, with only peregrine falcons showing trends towards larger and darker malar stripes in brighter regions. Falcon malar stripes are thus unlikely to represent an adaptation against visual effects of solar glare, and their adaptive significance is more likely to be explained by crypsis or social signalling, if indeed they do represent an adaptive trait. Malar stripes may have become co‐opted for solar glare reduction in peregrine falcons due to the species' specialisation for high‐speed aerial hunting, although the intraspecific patterns observed may alternately be explained by phylogeography. Keywords: avian colouration, dark eye markings, facial plumage, falcon, malar stripe, solar glare